Virus-specific antibody activity of different subclasses of immunoglobulins G and A in cytomegalovirus infections. - Linde, G A (1983)
Healthy donors and patients with primary or reactivated cytomegalovirus infections were examined for antiviral antibodies of the immunoglobulin G (IgG) and IgA subclasses. For this purpose, monoclonal antibodies against the four IgG and the two IgA subclasses were used in enzyme-linked immunosorbent assays with cytomegalovirus antigen. IgG1 and IgG3 were the principal anti-cytomegalovirus subclasses in serum samples from healthy donors and patients. IgG1 was higher in reactivated than in primary disease. Cytomegalovirus-specific IgG2 was detected only in serum samples with high total cytomegalovirus IgG. A few patients with high total serum IgG4 also had cytomegalovirus-specific IgG4 antibodies. During convalescence, there was no significant increase in total IgG of any subclass. Both IgA1 and IgA2 antibodies with cytomegalovirus specificity were detected in patients who had cytomegalovirus antibodies of the IgA class.